Relationship between bond and stock market performance in Malaysia, Singapore and south Korea. - Phang, Chia Yi (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study aim to examines the relationship between bond and stock market performance in Malaysia, Singapore and South Korea by using ordinary least square (OLS), correlation analysis, Augmented Dickey-Fuller (ADF) Unit Root, Johensen & Juselius (1&1) cointegration, Vector Error Correction Model (VECM) and Granger Causality test. The financial crisis will influence bonds and stock market performance.The findings of the study indicated that the bonds and stocks are positively relationship in Malaysia and Singapore but there is negative relationship between bonds and stocks in South Korea. The results are important in order to determine the asset allocation by investors and portfolio managers. In addition, the macroeconomic variables such as inflation rate, exchange rate and interest rate have been used in the regression models in order to determine the impact on macroeconomic variables towards the bond and stock market performance. The most influences variables for the relationship between bond and stock market is exchange rate in Malaysia and Singapore . However, inflation rate is the most influence variables in South Korea for the period 2001 to 2012. 2012.